Production of High-Purity Tantalum Metal Powder for Capacitors Using Self-Propagating High-Temperature Synthesis - Lee, Yong-Kwan; Sim, Jae-Jin; Byeon, Jong-Soo; Lee, Yong-Tak; Cho, Yeong-Woo; Kim, Hyun-Chul; Heo, Sung-Gue; Lee, Kee-Ahn; Seo, Seok-Jun; Park, Kyoung-Tae (Archives of Metallurgy and Materials, 2021)
In this study, high-purity tantalum metal powder was manufactured via self-propagating high-temperature synthesis. During the process, Ta2O5 and Mg were used as the raw material powder and the reducing agent, respectively, and given that combustion rate and reaction temperature are important factors that influence the success of this process, these factors were controlled by adding an excessive mass of the reducing agent (Mg) i.e., above the chemical equivalent, rather than by using a separate diluent. It was confirmed that Ta metal powder manufactured after the process was ultimately manufactured 99.98% high purity Ta metal powder with 0.5 µm particle size. Thus, it was observed that adding the reducing reagent in excess favored the manufacture of high-purity Ta powder that can be applied in capacitors.
Keywords: Tantalum; Self-propagating high-temperature synthesis; Tantalum Oxide; Magnesium; Capacitor